Australian cancer services: a survey of providers’ efforts to meet the needs of Indigenous patients - Taylor, E.; Haigh, M.; Shahid, Shaouli; Garvey, G.; Cunningham, J.; Holloway, M.; Thompson, S. (Wiley-Blackwell Publishing Asia, 2018)
© 2018 The Authors Objective: To examine where Indigenous Australians undergo cancer treatment and learn about specific service initiatives that have been implemented to meet their needs. Methods: Public cancer treatment centres across Australia were invited to participate in an online survey about various characteristics of their centre, including the type of service provided, Indigenous patient numbers and policy, and implementation of Indigenous-specific initiatives. Results: Surveys were completed for 58 of 125 public cancer treatment centres. Almost half (47%) of the services saw more than 10 Indigenous patients per year, although Indigenous patients generally represented a small minority of patients. The most commonly reported initiatives were “having links with Indigenous health organisations in the community” (74% of services), “making a dedicated effort to address the needs of Indigenous patients” (69%) and proactively “creating partnerships with Indigenous communities and health organisations” (69%). Conclusions: The majority of respondents indicated that they were working to meet the needs of Indigenous patients and were interested in learning strategies from others to improve their services. More work is needed to describe and evaluate the specific initiatives that have been implemented. Implications for public health: Information from this study can assist cancer service providers to identify gaps in current services, plan new service delivery initiatives and ultimately improve Indigenous cancer outcomes.